Antigen-specific tolerization approaches in multiple sclerosis. (January 2014) - Lutterotti, Andreas; Martin, Roland
<x xml:space="preserve">Abstract</x> Introduction: Inhibition of self-reactive T cells through induction of antigen-specific immune tolerance holds the promise of effective treatment of autoimmune pathology with few side effects and preservation of normal immune functions. In multiple sclerosis (MS) several approaches have been tested already in clinical trials or are currently ongoing with the aim to inhibit myelin-reactive immune responses. Areas covered: This article provides an overview of the recent and ongoing strategies to inhibit specific immune responses in MS, including different applications of myelin peptide-based approaches, T-cell vaccination, DNA vaccination and antigen-coupled cells. Expert opinion: Despite difficulties in translation of antigen-specific therapies in MS, novel approaches have the potential to effectively induce immune tolerance and ameliorate the disease. To improve efficacy of treatments, future trials should include patients in the early phases of the disease, when the autoimmune response is predominant and immune reactivity still focused. The target antigens are not fully defined yet, and robust immunomonitoring assays should developed to provide mechanistic proof of concept in parallel to showing efficacy with respect to inhibiting inflammatory disease activity in the central nervous system (CNS).